Fully printed and flexible multi-material electrochemical aptasensor platform enabled by selective graphene biofunctionalization. (1st March 2022) - Wallace, Shay Goff; Brothers, Michael C; Brooks, Zachary E; Rangnekar, Sonal V; Lam, David; Lawrence, Michael J St; Rojas, William A Gaviria; Putz, Karl W; Kim, Steve S; Hersam, Mark C
Abstract: The demand for flexible biochemical sensors has increased with advances in computational functionality and wireless communication. Advances in materials science and biochemistry have enabled the development and fabrication of biosensors for selective detection of biological analytes leveraging ink-printed technologies, including in flexible form-factors. However, despite these advances, minimal effort has been devoted to translating the multi-material, three-electrode electrochemical cell, which is widely regarded as the standard for laboratory-scale studies, into a flexible form-factor for use in immunosensors, especially in a manner that is compatible with rapid and scalable additive manufacturing. Here, we report a fully printed and flexible electrochemical non-enzymatic immunosensor platform that integrates four chemically compatible inks and a non-covalent, two-step biofunctionalization scheme. The robustness of the platform is demonstrated using a model aptasensor that enables lysozyme detection using both electrochemical impedance spectroscopy and square wave voltammetry. The flexible, fully ink-printed aptasensor shows competitive performance to commercially available rod/disc electrodes in a bath cell. Overall, this work establishes a methodology for high-throughput fabrication of robust, flexible, multi-material, three-electrode immunosensors that can be generalized to a range of biosensor applications.